The key to a secured cloud for businesses. (Research'eu results magazine)
Cloud storage may have been available for a while, but successful attacks on major providers have made companies wary of the consequences of entrusting it with their most sensitive data. Thanks to a secure framework developed under the PRACTICE project, these companies won't have to rely on cloud providers anymore to keep their data whole and confidential.